2012
DOI: 10.1155/2012/407023
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Root Sensitivity following Periodontal Therapy: A Systematic Review

Abstract: The reported prevalence of dentine/root (hyper)sensitivity (DH/RS) in the published literature varies, and this may be due in part to a) the different study populations and (b) the different methodologies employed in evaluating the pain response. According to von Troil et al. (2002) there are limited data available in terms of the prevalence and intensity of DH/RS following periodontal therapy. Objectives. The aim of the present study was therefore to review the literature in order to identify all relevant stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 44 publications
(208 reference statements)
0
60
1
1
Order By: Relevance
“…The present population‐based study provides additional evidence supporting previous clinical findings that periodontal treatment is related to the occurrence of DH. A recent systematic review of interventional studies 34 observed that different periodontal therapeutic strategies resulted in elevated dental sensitivity, although variations in duration and intensity may exist. Another Brazilian observational study conducted with dental patients found similar results 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The present population‐based study provides additional evidence supporting previous clinical findings that periodontal treatment is related to the occurrence of DH. A recent systematic review of interventional studies 34 observed that different periodontal therapeutic strategies resulted in elevated dental sensitivity, although variations in duration and intensity may exist. Another Brazilian observational study conducted with dental patients found similar results 23 .…”
Section: Discussionmentioning
confidence: 99%
“…10,28 The reported prevalence of DH following surgical therapy was 76.8-80.4% after 1 day, 29 36.8% after 1 week, 33.4% after 2 weeks, 29.6% after 4 weeks, and 21.7% after 8 weeks. 30 Although the removal of root cementum should be kept minimal, root instrumentation exposes dentinal tubules to the oral environment, thus exposing the dentin to a variety of bacterial, chemical, and mechanical stimuli. 31 DH usually reduces within a few weeks or months by formation of secondary dentin and natural occlusion of tubules by intertubular dentin.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature it is apparent that other terms are used to describe this clinical condition, for example, cervical dentine sensitivity (CDS), cervical dentine hypersensitivity (CDH), dentine sensitivity (DS) or root dentine sensitivity (RDS)/root dentine hypersensitivity (RDH), which describes sensitivity arising from periodontal disease and its treatment. However, the sensitivity that occurs following periodontal therapy may be distinct from the DH that occurs after hydrodynamic stimulation. To date, the term ‘dentin hypersensitivity’ has been preferred in the published literature, partly because of its historical significance.…”
Section: Introductionmentioning
confidence: 99%